Trends and factors associated with the nutritional status of adolescent girls in Ghana: A secondary analysis of the 2003-2014 Ghana Demographic and Health Survey (GDHS) data - Azupogo, Fusta; Abizari, Abdul-Razak; Aurino, Elisabetta; Gelli, Aulo; Osendarp, Saskia J. M.; Bras, Hilde; Feskens, Edith J.; Brouwer, Inge D. (Cambridge University Press, 2022)
Objective: We examined the trends over time and the factors associated with malnutrition among adolescent girls in Ghana.